Statins Reduce Postoperative VTE after Total Knee or Hip Replacement - Nichols, Emma Hitt (MD Conference Express, 2014)
Statins reduce postoperative venous thromboembolism (VTE) events in patients undergoing elective total knee arthroplasty or total hip arthroplasty. This article presents data from a retrospective study that evaluated the effect of statin use on postoperative VTE in patients who had undergone total knee or hip replacement.